2014
DOI: 10.5812/jjm.12676
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori in Patients With Dyspepsia

Abstract: Background:The prevalence rate of gastric infections caused by Helicobacter pylori is different in between as well as within various countries, including Iran.Objectives:This study was aimed to evaluate the prevalence of H. pylori in Iranian adult patients with dyspepsia.Patients and Methods:A total of 548 patients with dyspepsia referred to Namazi Hospital, a referral center for gastrointestinal diseases in Shiraz, south of Iran, were evaluated in a cross-sectional study. The diagnosis of dyspepsia was based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
26
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 16 publications
10
26
2
1
Order By: Relevance
“…Females in this study were 1.54 times more likely to have H. pylori infection. Similar data were seen in the Iranian population, but the opposite was found in the Brunei population . In Malaysia, there was no difference of H. pylori infection between genders in the Kota Kinabalu city and in north‐eastern Peninsular Malaysia .…”
Section: Discussionsupporting
confidence: 73%
“…Females in this study were 1.54 times more likely to have H. pylori infection. Similar data were seen in the Iranian population, but the opposite was found in the Brunei population . In Malaysia, there was no difference of H. pylori infection between genders in the Kota Kinabalu city and in north‐eastern Peninsular Malaysia .…”
Section: Discussionsupporting
confidence: 73%
“…However, it has been reported that H. pylori prevalence has now started to decline in Asia and the Middle East (26)(27)(28). In a recent study using culturing, Gram staining, and rapid urease test, we reported the H. pylori positivity of 31% in 548 dyspeptic patients of Fars province with both rural and urban nature of lifestyle, Iran, which was surprisingly lower than other local reports (29). Regarding these differences, it can be said that high prevalence of H. pylori infection is related to socioeconomic status, poor living conditions, and poor management of drinking water (30,31).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 43%
“…The stool Ag positivity of H. pylori was related with age, increasing with age up to 41 -50 years category and then decreasing. Helicobacter pylori is typically acquired in early childhood in developing countries and usually persist during lifetime if left untreated (29), however, the H. pylori infection rate increases with age in adults (32). Although, serum assaying of anti-H. pylori IgG or IgA antibodies could be used to determine prevalence of infection (33), stool antigen test, as a non-invasive test, could be used both safely and cost effectively to screen patients (34,35).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…But in USA by R. P. Jackman, et al [40] was only (10.4%). The reason for the difference in the prevalence of H. pylori positivity is probably due to varying sample size; age groups, geographical locations, socioeconomical factors and time periods the studies were carried out.…”
Section: Discussionmentioning
confidence: 91%